Condyloma acuminata in pregnancy: clinical profile and management - Auxeelia P. D. R. Rathinasamy; Lalitha Karunamoorthy; Bhavadharani Nanthakumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Condyloma acuminatum, also known as mucocutaneous external genital warts, is a benign neoplasm of the genital tract caused by human papillomavirus most commonly types 6 and 11. Here we present a case of 24-weeks unbooked primigravida who presented with complaints of vulval itching and a mass over the vulva for six months. Genital examination revealed multiple papillomatous growths arising from the vulva, no bleeding on touch. At 24 weeks of gestation vulval biopsy was performed and the report showed condyloma acuminatum. She presented in early labor pain with complete spontaneous resolution of the lesions at 39 weeks of gestation. She underwent a spontaneous vaginal delivery. Both mother and neonate were healthy in the postnatal period. This case highlights that condyloma acuminatum may regress spontaneously during pregnancy and is not an indication for caesarean section.